#TITLE_ALTERNATIVE# - (NIM 10203037), AMALIA
Tsunami is wave that happens after an earthquake on the sea floor. The main cause of this wave is the fracture of the sea floor due to an earthquake. Compared to earthquake, tsunami may have bigger impact. That is why people need someway to detect tsunami before it reaches the shore. The Tsunami Early Warning System is used to detect every tsunami that occurred in the ocean and gives warnings for people. The basic principle of the system is to know the water level differences that happen in a very short time. The Tsunami Early Warning System is made with three main parts: Sensor, ADC, and PC. The sensor is used to measure the water level. Then, the data is received by the ADC and then to PC. At Personal Computer, the data is processed and plotted. The received data is compared to the reference one to decide whether it is a tsunami or not. If the result is tsunami, the program will issue an audio and visual warning.